I can drive again / Dr. Akehsan Dahlan … [et al.] - Dahlan, Dr. Akehsan; Masuri, Mohamad Ghazali; Sultan Ibrahim, Syamsul Anwar; Mohd Yazid, Fadzli Syadiqin; Murad, Dr. Mohd. Suleiman (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Occupational therapy department in UiTM has collaborated with Road Transport Department (Jabatan Pengangkutan Jalan), Malaysia to designed and modify a car to cater the need for driving from special need person, for example people with stroke, lower limb amputations, hand dysfunction, paraplegia patients and patients with arthritis. The design is unique to each individual limitation. This will help the special need person to be able to drive and be independent in daily life. Previous studies indicated that being able to drive again will contribute significantly to quality of life especially for older people and people with disability (Owsley et al., 2002; Decalo et al., 2003; Edwards, et al., 2006; Hitosugi et al., 2011; Tinmen, et al., 2011). The modification and adaptation to a vehicle has a great value and high potential for commercialisation.